Revisão Sistemática de Literatura do modelo de governança da Fundação Renova: subsídios para uma análise crítica - Dinat, Camila (2022)
As a result of the failure of the Fundão iron ore tailings dam on November 5, 2015, in Mariana (MG), an environmental crime that resulted in death, a Transaction and Conduct Adjustment Agreement (TTAC) was signed between the responsible companies Samarco, Vale and BHP Billiton, and public institutions at the federal and state levels of MG and ES. The TTAC defined the creation of the Renova Foundation for exclusive dedication to the process of repairing the damage caused. It was necessary to establish a robust governance model, on which there clearly seems to be no consensus regarding the effectiveness in the face of the proportions of the disaster. To understanding the proposed model, a systematic literature review (RSL) was carried out to identify the state of the art, and in the light of good governance principles, the study sought to identify the critical points of the system. The result of the RSL was the classification of the literature in three complementary perspectives of analysis: i) governance from the point of view of public policy; ii) the governing and participatory logics present in the model; and iii) criticism from the point of view of deliberative democracy. The study concludes that public authorities, environmental agencies and institutional arrangements in environmental matters, have shown themselves to be unprepared to promote disaster management of this magnitude, which culminated, among other definitions, in a governance structure to perform such management, inadequate. The critical points identified can suggest ways to improve the current system.